Аналіз засобів розробки мультимедійного ігрового контенту засобами середовища python на прикладі гри «змійка» - Гришко, А. Д. (ХНУРЕ, 2023)
The Snake game is quite a fun and entertaining game that can keep players busy for a few minutes or hours. Nowadays, the game is available on various platforms - from classic arcade machines to mobile devices and various computers. It is also worth noting that some developers create new versions of the snake game, adding new elements and functions, which makes the game even more interesting and attractive for players.
Keywords: ігровий контент; середовище python